On the incorporation of the non-steroidal anti-inflammatory naproxen into cationic O/W microemulsions - Correa, Marcos Antonio [UNESP]; Scarpa, M. V.; Franzini, M. C.; Oliveira, Anselmo Gomes de [UNESP] (Elsevier B.V., 2005)
Microemulsions (ME) containing hexadecyltrimethylammonium bromide (HTAB)/ethanol as surfactant, isopropylmyristate (IM) or butylstearate (BS) as oil phase and aqueous buffer were studied. Pseudo-ternary phase diagrams of the investigated systems were obtained at constant surfactant/cosurfactant molar ratio (1:5) by titration in order to characterize the proportions between the components to obtain clear systems. Oil in water microemulsions were prepared in a wide range of phase volume (phi). UV-vis absorption spectra of naproxen at pH 5.5 showed that the solubility of Np increases significantly in the presence of O/W ME in high phase volumes. For both, IM and BS microemulsions, the dynamic light scattering experiments showed that the size of the oil droplets remains constant in low values of phi, increasing abruptly in high phi values. Phase solubility study revealed that for both IM and BS microemulsions, the drug incorporation followed a straight-line profile in all range of phi. The data could be analyzed through the phase-separation model and the association constants (K) calculated varied from 27 to 90 M-1, depending on the pH and on the microemulsion oil phase. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: naproxen; microemulsion; hexadecyltrimethylammonium bromide; non-steroidal anti-inflammatory